Female infanticide and child marriage - Goswami, Sambodh (Jaipur : Rawat Publications, 2007)
Study with special reference to Rajasthan, India.
Includes bibliographical references (p. [393]-405) and index.
Includes passages in Rajasthani.
Keywords: Female infanticide -- India -- Rajasthan; Child marriage -- India -- Rajasthan; Infant girls -- Violence against -- India -- Rajasthan